Single Nucleotide Gene Polymorphism of Interleukin 1 Receptor Gene at Position-1970 in Type 1 Diabetes of Iraqi Patients - Ibtesam Badday Hassan (Journal of Global Pharma Technology, 2018)
The aim of this study was to evaluate the frequency of polymorphism of interleukin-1-R gene (IL1R) at position-1970 SNP) in T1D and in healthy controls subjects39 of Iraqi patients, (12 males & 27 females;1 5.65 ± 1.79 years) and 21 controls.(7 mail & 14femal ; 14.66 ± 3.43 years) were enrolled in this study the polymorphism of IL-1R-1970was data waved by polymerase chain reaction-specific sequence primer (PCR-SSP) assay. Results revealed that comparing IL1R-1970genotypes and alleles between T1D patients and controls frequencies of TC genotype and C allele (79.49vs. 68.05%;P =0.419respectively) were significantly rise in patients contrast to controls, (38.28vs. 40.62%; P =0.094) and the related RR rates were 21.3%and39.8%, respectively. And the associated EF values were 1.71and2.11.Similar observations were made in CC genotype. In contrast TT genotype and T allele (22.33vs. 38.95%, P =0.706respectively) frequencies were significantly decreased in patients, compared to controls (42.38vs. 49.38%; P =0.094), and associated PF values were 0.63and0.47, respectively. These findings suggest that IL1R-1970 SNP might have a role in the etiopathogenic mechanism showed associations (positive and negative) with T1Din the samples of Iraqi patients.Keywords: SNP IL-1R Diabetes.